Fracture through fused cervical segments following trauma in a patient with Klippel–Feil syndrome. (June 2014) - Al-Tamimi, Yahia Z.; Sinha, Priyank; Ivanov, Marcel; Robson, Craig; Goomany, Anand; Timothy, Jake
Abstract Klippel–Feil syndrome (KPS) is a congenital spinal deformity characterised by the presence of at least one fused cervical segment. We report an unusual case of a fracture through fused cervical segment in a patient with KPS, who presented with quadriparesis and progressed on to develop respiratory failure and quadriplegia and who had a successful outcome following surgery. To the best of our knowledge, fracture through fused cervical segments in a Klippel–Feil patient has not been reported previously and this case report extends the spectrum of injuries seen in patients with KPS.